Effect of The Composition of Hydrophobic Agents on The Contact Angle and Strength of Mortal Cement. Issue 1 (1st July 2022) - Salam, Muhammad; Rokhmat, Mamat; Rustam, Rusnardi
Abstract: Mortar cement resistance has serious economic implications in the form of maintenance costs and replacement of a structure. Therefore it is necessary to make cement mortar that is waterproof or hydrophobic. The purpose of this study was to look at the effect of the composition of hydrophobic agents on the large contact angle and strength of mortal cement. The hydrophobic agent used is Tetrahydrofuran (THF) with polyurethane (PU) with variations of 5:6molar, 1:10molar, 1:10.9 molar with total each variation being 11 molars. The control variables in this study are the amount of composition of otawa sand, aquades and silica sand 20-30 mesh which is 4:11:2 mold 5 cm x 5cm cement mortar cubes, long immersion with Ca(OH)2 10% for 7 days, temperature 60 °C and heating length 1 hour. The large angle of contact is measured using the caessyal drop method and the hardness value using the hardness vickers tool. The results showed that the higher the concentration of Polyuteran, the smaller the contact angle of mortar cement produced. The largest contact angle occurs at the concentration of THF variation: PU 6:5 mol. The optimum contact angle is 126° and the mortal seemen are hydrophobic.